IMPLEMENTATION OF FRAMEWORK DECISIONS REGARDING SUBSTANTIVE CRIMINAL LAW INTO THE POLISH LEGAL ORDER – SELECTED ISSUES - RADONIEWICZ, Filip (Comparative Legilinguistics, 2012)
The paper is composed of three basic parts. In the introduction are discussed the successive stages of cooperation of the states of the European Union within the III pillar of the EU – from its inception (the European Union Treaty, signed in Maastricht on the 7th of February 1992) to the Treaty of Lisbon (signed on the 13th of December 2007). In the second part is described the most significant legal instrument of the III pillar, implementing the harmonisation of the criminal law of the member states, that is the framework decisions. In the third part are presented examples of the implementation of chosen framework decisions in Polish law – the Framework Decision of the Council of 2002/475/JHA of 13th of June 2002 on combating terrorism and the Framework Decision of the Council 2002/629/JHA of the 19th of July 2002 on combating trafficking in human beings. Certainly the choice is not casual. The author endeavours to present two extreme models of implementing of framework decisions: a method of implementation consisting in transfer of legal rules, with the aim of inserting created norms into the Polish legal order and the contrary one of rewriting the content of the implemented framework decision without any reflection.